Application of the Material Balance Equation Based on the BET Multimolecular Fractal Theory in a Shale Gas Reservoir - Qiu, Tingting; Hu, Shuyong; Zhang, Jiayi (Frontiers in Energy Research, 2022)
During shale gas reservoir development, obtaining actual formation pressure is challenging; therefore, it is challenging to obtain a single well production allocation using current formation pressure based on a productivity equation. Different shale gas reservoirs with different rock adsorption properties and the traditional Langmuir isotherm adsorption equations are not accurate in describing the adsorption properties of shale gas reservoirs, causing significant errors. BET multimolecular adsorption, considering the shale gas surface fractal dimension theory to describe the adsorption properties, can describe the adsorption surface as a multimolecular layer and regard the adsorbate using a fractal dimension, describing the adsorption property of a shale gas more accurately. According to the core adsorption test data and theory, the actual BET multimolecular adsorption is established by considering the shale gas surface fractal dimension. Therefore, the actual material balance equation was obtained using the theory, establishing the relationship between formation pressure and cumulative shale gas production, and a time-independent distribution and cumulative gas production chart were formed using the productivity equation. Consequently, the material balance equation, which takes advantage of the BET multimolecular fractal theory, was conducted. This allocation production method obtained from the material balance equation has significant importance in shale gas development.